2015
DOI: 10.12703/p7-53
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the management of basal cell carcinoma

Abstract: Basal cell carcinoma (BCC), a malignant neoplasm derived from non-keratinizing cells that originate in the basal layer of the epidermis, is the most common cancer in humans. Several factors such as anatomic location, histologic features, primary or recurrent tumors, and patient characteristics influence the choice of treatment modality for BCC. Mohs micrographic surgery (MMS) facilitates optimal margin control and conservation of normal tissue for the management of BCC; however, other treatment modalities may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 64 publications
2
32
0
4
Order By: Relevance
“…This study observed a success rate of 89% for ED&C. Although finding the success rate of ED&C was not the primary purpose of this study, our success rate correlates well with previous research showing success rates between 84 and 98% [6,7,10,11] . There are several potential confounding variables.…”
Section: Discussionsupporting
confidence: 88%
“…This study observed a success rate of 89% for ED&C. Although finding the success rate of ED&C was not the primary purpose of this study, our success rate correlates well with previous research showing success rates between 84 and 98% [6,7,10,11] . There are several potential confounding variables.…”
Section: Discussionsupporting
confidence: 88%
“…BCC is derived from non-keratinizing cells of the basal layer of the epidermis, generally grows slowly and rarely metastasizes [30]. Current treatment options of BCC include standard excision, Mohs micrographic surgery, electrodesiccation and curettage, cryosurgery, radiation therapy, photodynamic therapy, 5-fluorouracil or imiquimod (an immune modifier) and for extensive cases hedgehog signaling pathway inhibitors such as vismodegib [31]. SCC accounts for about 20% of non-melanoma skin cancers and originates from squamous cells of the epidermis, typically forming slowly growing nodules which may ulcerate.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime risk of developing NMSC is estimated to be one in five, with the majority of cases being basal cell carcinoma (BCC). 1 Incidence of BCC increases with age, with the main risk factor being ultraviolet exposure. 2 Patients with a diagnosed BCC are at significantly higher risk of developing subsequent lesions.…”
Section: What Does This Study Add?mentioning
confidence: 99%